Watering a lemon tree: Heterogeneous risk taking and monetary policy transmission - Choi, Dong Beom; Eisenbach, Thomas M.; Yorulmazer, Tanju (Journal of Financial Intermediation, 2021)
We build a general equilibrium model with financial frictions that impede monetary policy transmission. Agents with heterogeneous productivity can increase investment by levering up, which increases liquidity risk due to maturity transformation. In equilibrium, more productive agents choose higher leverage than less productive agents, which exposes the more productive agents to greater liquidity risk and makes their investment less responsive to interest rate changes. When monetary policy reduces interest rates, aggregate investment quality deteriorates, which blunts the monetary stimulus and decreases asset liquidation values. This, in turn, reduces loan demand, decreasing the interest rate further and generating a negative spiral. Overall, the allocation of credit is distorted and monetary stimulus can become ineffective even with significant interest rate drops.